PENGALAMAN PEREMPUAN DALAM DUNIA KERJA DI INDUSTRI TEKNOLOGI INFORMASI - Anita, Julia (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2022)
This research aims to understand women's experiences in the world of work in the information technology industry in Kabupaten Tanjung Jabung Barat, Jambi, focusing on the challenges faced, the strategies used to overcome these challenges, and the impact of corporate policies on gender equality. The data was collected through in-depth interviews, participatory observations, and documentation analysis at one of the information technology companies in Kabupaten Tanjung Jabung Barat, Jambi. The findings show that women often face gender stereotypes, difficulties in balancing work and personal life, and barriers to getting promotions and recognition for their achievements. To address these challenges, women use a variety of strategies, including building support networks, attending training and skill development, and effective time management. Although the company has implemented various policies to support gender equality, its implementation still encounters various obstacles. This research provides recommendations to improve the effectiveness of gender equality policies and create a more inclusive and equitable work environment.